Architecture for the Creation of Ubiquitous Services Devoted to Health (2019)
Ubiquitous systems have several applications in many fields such asindustry, education and health. In terms of health, they are used to supportboth the patient and health professionals in order to improve healthcare,through efficient access to critical information, diagnosis, treatment, andmonitoring of the patient.Ubiquitous computing is a concept that has gotten great importance aroundthe world where major projects about this topic are being developed.Current developments in data wired and wireless networks in terms ofreliability and bandwidth support, that have allowed the efficient use ofthese networks for the transport of multimedia traffic, as well as progressin building sensors and other wireless devices becoming more efficientin terms of battery consumption, have propitiated the development ofubiquitous systems.This article shows the design of a common architecture for the developmentof ubiquitous systems in the health domain for monitoring physiologicaland context variables of patients under clinical control.